Unusual Ileal Anomalies Associated with Omphalomesenteric Duct Remnants - Mohamed Ouladsaiad; Najoua Aballa; El Ouafi El Aouni Kamili; Karima Fouraiji (Wolters Kluwer Medknow Publications, 2017)
The association between omphalomesenteric duct remnants and other digestive tract malformations is not rare. Most associated anomalies are reported with Meckel's diverticulum. We report two associated anomalies which were never reported: an ileal stenosis and an ileal duplication. Surgeons must be aware of associated anomalies to prevent post-operative complications.